Pengaruh Kepribadian, Keberanian Mengambil Risiko, Ekspektasi Pendapatan Terhadap Minat Berwirausaha Mahasiswa Universitas Slamet Riyadi Surakarta - Cintapuri Sapta Alury; Riska Fii Ahsani (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research aims to analyze the significance of the influence of personality, courage to take risks, income expectations on students' interest in entrepreneurship at Slamet Riyadi University, Surakarta. The types of data used in this research are quantitative. The data sources used are primary and secondary data. The sample in this research was 100 students at Slamet Riyadi University, Surakarta. The method used in sampling was proportional random sampling. Data collection techniques in this research used questionnaires. Test the research instrument using validity and reliability tests. The classical assumption test uses tests: multicollinearity, autocorrelation, heteroscedasticity and normality. Data analysis techniques use multiple linear regression tests, t tests, F tests, and R2. The results of the validity and reliability tests show that all statements regarding personality, courage to take risks, income expectations and interest in entrepreneurship are declared valid because the p-value is < 0.05 and reliable because Cronbach's alpha is > 0.60. The results of the classical assumption test show that all variables have passed the multicollinearity, heteroscedasticity, autocorrelation and normality tests with normal distribution. The results of the regression analysis obtained the equation Y = .612 + 0.221 X1 + 0.326 X2 + 0.556 X3 + e. The results of the t test show that personality (X₁), courage to take risks (X₂), and income expectations (X₃) have a significant effect on students' interest in entrepreneurship at Slamet Riyadi University, Surakarta. The results of the F test showed that the regression model used in this research was correct. The R² test results show that the contribution of the independent variable to the dependent variable is 45.5%, the remaining 54.5% is influenced by other factors outside the variables studied